Inhibition of BET proteins modulates amyloid-beta accumulation and cognitive performance in middle-aged mice prenatally exposed to maternal immune activation - Matuszewska, Marta; Wilkaniec, Anna; Gąssowska-Dobrowolska, Magdalena; Cieślik, Magdalena; Olech-Kochańczyk, Gabriela; Pałasz, Ewelina; Gawinek, Elżbieta; Strawski, Marcin; Czapski, Grzegorz A. (Frontiers in Molecular Neuroscience, 2025)
IntroductionGiven the complex etiological basis of Alzheimer’s disease (AD), it is reasonable to hypothesize that neuronal dysfunction and death result from the interplay of numerous factors, both genetic and environmental. Accumulating evidence implicates the immune system and inflammation as key components of the pathomechanism of AD. In the present study, we analyzed the effect of maternal immune activation (MIA) on AD-related pathological changes in middle-aged 12-month-old offspring mice. Additionally, we investigated whether the inhibition of bromodomain and extraterminal domain (BET) proteins, which are readers of the histone acetylation code, could influence these changes.MethodsIn our study, we administered a viral mimetic, polyinosinic-polycytidylic acid (PIC), on gestation day 17 to induce MIA in wild-type C57BL/6J mice. The BET protein inhibitor, OTX-015 (Birabresib), was administered orally to 12-month-old male offspring for 14 days. Subsequently, behavioral, genetic, and immunochemical analyses were conducted.ResultsOur results demonstrated several MIA-evoked molecular alterations in the brains of middle-aged offspring. We observed an increase in App gene expression (qPCR) and amyloid-β (Aβ) levels (ELISA), while the levels and phosphorylation of Tau protein remained unchanged (WB). The mRNA levels of selected microglial markers were also elevated in the MIA group. Treatment with OTX-015 improved memory, as observed in the novel object recognition test, and reduced Aβ levels, but did not alter the expression of inflammatory genes or amyloidogenesis-related genes.DiscussionOur findings suggest that inhibition of BET proteins may effectively attenuate neuropathological alterations in the aged brain.